A novel HLA‐C allele, HLA‐C*03:614, identified by next‐generation sequencing in a Chinese individual. (9th November 2022) - Wang, Yan; Ma, Junxia; Liu, Keyao; Wang, Linlin
Abstract : HLA‐C*03:614 has one nucleotide change compared with HLA‐C*03:02:02:01 in exon 7, codon 336.